Analysis Of Bed Utilization Efficiency In Welas Asih Hospital Of West Java Province Per Inpatient Room Based On Inpatient Indicators In 2024 - Fauzan Elang Dirgantara; Rizqy Dimas Monica; Matoeari Soelistijaningroem (CV. AFDIFAL MAJU BERKAH, 2025)
The efficient utilization of hospital beds is a crucial indicator for evaluating the quality of inpatient services. This study aims to analyze the efficiency of bed utilization per inpatient room at Welas Asih Regional Hospital in West Java Province throughout 2024. Using a quantitative descriptive approach, the research sourced secondary data from the Daily Inpatient Census (SHRI) from January to December 2024. The study population and sample comprised data from all 24 inpatient rooms, with data analysis performed using standard formulas from the Ministry of Health. The results show that the overall Bed Occupancy Rate (BOR) was 89% (not ideal), the Average Length of Stay (AVLOS) was 3 days (not ideal), the Turn Over Interval (TOI) was 0 days (not ideal), and the Bed Turn Over (BTO) was 94 times per year (not ideal). Only one room, Salman Al Farizi Level 3 NICU, met all four ideal indicators. These discrepancies are attributed to high demand, limited bed capacity, and suboptimal service management. In conclusion, bed utilization efficiency at Welas Asih Regional Hospital remains suboptimal and requires a comprehensive evaluation and system improvement.